Membangun dan Mengelola Web sebagai Pengetahuan Teknologi Informasi Guru SMP Bina Bangsa Mandiri Cikeas Kabupaten Bogor - Senna Hendrian; Ambar Tri Hapsari; Een Juhriah; Dewi Leyla Rahmah; Riezca Talita Trista (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2025)
The rapid advancement of information technology requires teachers to possess adequate digital skills and understanding to support the learning process. A website serves as an essential digital medium that can be utilized for providing information, learning materials, activity documentation, and facilitating communication among teachers, students, and the school. This study aims to develop and manage a school website as a means to enhance information technology knowledge for teachers at SMP Bina Bangsa Mandiri Cikeas, Bogor Regency. The research employed a system development approach, including needs analysis, design, implementation, and evaluation of website usage by teachers. The results indicate that the developed website provides ease of access in managing school information, preparing digital learning content, and improving teachers’ digital literacy. Moreover, the website serves as a collaborative platform that supports teachers in sharing materials and teaching innovations. Therefore, developing and managing a website effectively contributes to enhancing information technology competence among junior high school teachers.